Transcriptional over-expression of chloride intracellular channels 3 and 4 in malignant pleural mesothelioma. (December 2015) - Tasiopoulou, Vasiliki; Magouliotis, Dimitrios; Solenov, Evgeniy I.; Vavougios, Georgios; Molyvdas, Paschalis-Adam; Gourgoulianis, Konstantinos I.; Hatzoglou, Chrissi; Zarogiannis, Sotirios G.
Graphical abstract: Highlights: CLIC3 and CLIC4 gene expression is induced in malignant pleural mesothelioma. CLIC3 and CLIC4 gene expressions are significantly positively associated. Functional Enrichment for GO reveals a role in EMT pathways and water transport. Abstract: Background: Chloride Intracellular Channels (CLICs) are contributing to the regulation of multiple cellular functions. CLICs have been found over-expressed in several malignancies, and therefore they are currently considered as potential drug targets. The goal of our study was to assess the gene expression levels of the CLIC's 1–6 in malignant pleural mesothelioma (MPM) as compared to controls. Methods: We used gene expression data from a publicly available microarray dataset comparing MPM versus healthy tissue in order to investigate the differential expression profile of CLIC 1-6. False discovery rates were calculated and the interactome of the significantly differentially expressed CLICs was constructed and Functional Enrichment Analysis for Gene Ontologies (FEAGO) was performed. Results: In MPM, the gene expressions of CLIC3 and CLIC4 were significantly increased compared to controls ( p = 0.001 and p < 0.001 respectively). A significant positive correlation between the gene expressions of CLIC3 and CLIC4 ( p = 0.0008 and Pearson's r = 0.51) was found. Deming regression analysis provided an association equation between the CLIC3 and CLIC4 gene expressions: CLIC3 = 4.42CLIC4–10.07. Conclusions: Our results indicate that CLIC3 and CLIC4 are over-expressed in human MPM. Moreover, their expressions correlate suggesting that they either share common gene expression inducers or that their products act synergistically. FAEGO showed that CLIC interactome might contribute to TGF beta signaling and water transport.